Clinical Teaching in Forensic Medicine: Need of the Hour - Mohite, Prakash M; Anjankar, Anil J; Srivastava , Tripti (Journal of Indian Academy of Forensic Medicine, 2015)
Forensic Medicine is a medical specialty that is practiced at the interface with the law. Keeping in view the increasing incidences of allegations against health professionals it is necessary to impart practical training to medical graduates in various Medico-legal cases to make them well oriented with the procedures & proper documentation. Total 138 students of 2nd M.B.B.S of J.N.MC participated in this study. The exercise of Examination & certification of an Injury was given to the student. Students were informed about this exercise. Bedside teaching students were exposed to examination to interpret the injuries present. The impact of the clinical exposure on the students was carried out through structured questionnaire. The student’s feedback was taken in the form of Pre & Post-test. This feedback evaluation was used to assess the significance of this newer teaching methodology. Statistically significant results were observed from the response given by the students to each structured question. It is need of the hour to reframe the under graduate curriculum and introduce clinical posting for them in the subject of Forensic Medicine for making a competent medical graduates to handle the cases of Medico legal importance.